Digital Dilemma : Human Rights in the Era of Cyber Crimes - Bhouradia, Rupali; Tyagi, Richa (Trinity Law Review, 2024)
The rapid pace of digitalization is reshaping the landscape of human rights, presenting both opportunities and challenges. While digital technologies have facilitated unprecedented access to information, communication, and economic opportunities, they have also introduced new risks to fundamental human rights. From privacy infringements and online surveillance to the spread of disinformation and cybercrimes, the digital era presents a complex ethical dilemma that requires careful consideration. At its core, human rights remain paramount in navigating this digital information. The present paper shall explore the potential of digital technologies; it is imperative to prioritize human rights as the cornerstone of ethical and responsible digitalization efforts, ensuring that technology serves humanity’s collective well-being and advances the principle of equality, justice, and dignity for all. It shall highlight the major challenges posed to human rights by cyber offenses such as privacy violations, freedom of expression, access to information, threat to critical infrastructure, etc. The secondary method is employed by the scholar for the collection of data.4